IN-SILICO STUDIES FOR COMPARATIVE ANALYSIS OF GLUTATHIONE PEROXIDAES ISOZYMES IN HOMO - SHAILESH KUMAR; KIRTI BHADHADHARA; SUMIT GOVIL; NIDHI MATHUR; A. N. PATHAK (International Journal of Pharma and Bio Sciences, 2014)
Glutathione peroxidase (GPx) is a family of protein, which is responsible for eradication of various reactive molecules like H2O2 and other peroxidase helps in protection from oxidative degeneration. In humans, there are 8 different isozymes of GPx families GPx1-GPx8 are isolated from various tissues. The sequence and structure based analysis of these isozymes are studied to find differences among them. Here sequence analysis is carried by MEGA6.06 software where MUSCLE an iterative alignment program was used to find multiple sequence alignment, which represents 32 conserved sites, evolutionary distances, mutation rates based on 154 sites without gap and missing residues. Structural comparison done by SPDBV based Magicfit tool to carry out carbon alpha and all atoms based structural superimposition. The results obtained by Sequence and Structure based comparison insights that there are three groups in isozymes based on evolution Group 1: GPx7, GPx8 and GPx4, Group 2: GPx1 and GPx2 , Group 3: GPx3, GPx5, and GPx6.